An Optimized Circuit in Plastic Meander Line Antenna for 2.45 GHz Applications - Farhat Majeed; David V. Thiel (International Journal of Antennas and Propagation)
Researchers seek to design electrically small planar antennas for RFID applications. Using multiparameter optimization, various meander line antennas were designed for the lowest resonant frequency and maximum radiation efficiencies for a fixed grid size. One such design for highest radiation efficiency was optimized for microwave frequencies by including an impedance matching structure. The antenna was printed with silver ink on a plexiglass substrate using the circuit in plastic (CiP) technique of embedded electrical components. The measured scattering parameter (S11) was −18.43 dB at resonance. The radiation efficiency of the antenna measured using simple and improved Wheeler cap method was 74.4/74.1%. The radiation pattern of electrically small CiP antenna was doughnut-shaped with main lobe magnitude of 0.453 dB and an angular width of 84.2° in elevation plane. The measured 10 dB fractional bandwidth of the antenna was 18.98%. The results are compared with silver/copper in air antennas optimized for achieving the highest radiation efficiency for a fixed grid size. Plastic antennas are viable at microwave frequencies.